Pharmacokinetics and Pharmacodynamics of Colistin Combined With Isopropoxy Benzene Guanidine Against mcr-1-Positive Salmonella in an Intestinal Infection Model - Kong, Lingli; Lu, Yixing; Yang, Liuye; Zhang, Wanying; Zuo, Beini; Peng, Xianfeng; Qin, Zonghua; Li, Miao; Zeng, Zhenling; Zeng, Dongping (Frontiers in Microbiology, 2022)
Plasmid-borne colistin resistance mediated by mcr-1 is a growing problem, which poses a serious challenge to the clinical application of colistin for Gram-negative bacterial infections. Drug combination is one of the effective strategies to treat colistin-resistant bacteria. Here, we found a guanidine compound, namely, isopropoxy benzene guanidine (IBG), which boosted the efficacy of colistin against mcr-1-positive Salmonella. This study aimed to develop a pharmacokinetics/pharmacodynamics (PK/PD) model by combining colistin with IBG against mcr-1-positive Salmonella in an intestinal infection model. Antibiotic susceptibility testing, checkerboard assays and time-kill curves were used to investigate the antibacterial activity of the synergistic activity of the combination. PK studies of colistin in the intestine were determined through oral gavage of single dose of 2, 4, 8, and 16 mg/kg of body weight in broilers with intestinal infection. On the contrary, PD studies were conducted over 24 h based on a single dose ranging from 2 to 16 mg/kg. The inhibitory effect Imax model was used for PK/PD modeling. The combination of colistin and IBG showed significant synergistic activity. The AUC0−24h/MIC index was used to evaluate the relationship between PK and PD, and the correlation was >0.9085. The AUC0−24h /MIC targets in combination required to achieve the bacteriostatic action, 3-log10 kill, and 4-log10 kill of bacterial counts were 47.55, 865.87, and 1894.39, respectively. These results can facilitate the evaluation of the use of IBG as a potential colistin adjuvant in the treatment of intestinal diseases in broilers caused by colistin-resistant Salmonella.